The natural history of spinal neurofibromatosis: a critical review of clinical and genetic features. (22nd November 2014) - Ruggieri, M.; Polizzi, A.; Spalice, A.; Salpietro, V.; Caltabiano, R.; D'Orazi, V.; Pavone, P.; Pirrone, C.; Magro, G.; Platania, N.; Cavallaro, S.; Muglia, M.; et al.
<x xml:space="preserve">Abstract</x> Spinal neurofibromatosis (SNF) is a related form of neurofibromatosis 1 (NF1), characterized by bilateral neurofibromas (histologically proven) of all spinal roots (and, eventually, of all the major peripheral nerve branches) with or without other manifestations of classical NF1. By rigorous application of these criteria to the 98 SNF cases published, we developed: (i) a cohort of 49 SNF patients (21 males and 28 females; aged 4–74 years]: 9 SNF families (21/49), 1 mixed SNF/NF1 family (1/49) and 27 of 49 sporadic SNF patients (including 5 unpublished patients in this report); and (ii) a group of 49 non‐SNF patients including: (a) 32 patients with neurofibromas of multiple but not all spinal roots (MNFSR): 4 mixed SNF/MNFSR families (6/32); (b) 14 patients with NF1 manifestations without spinal neurofibromas, belonging to SNF (8/49) or MNFSR families (6/32); (c) 3 patients with neurofibromas in one spinal root. In addition to reduced incidence of café‐au‐lait spots (67% in SNF vs 56% in MNFSR), other NF1 manifestations were less frequent in either cohort. Molecular testing showed common NF1 gene abnormalities in both groups. The risk of developing SNF vs NF1 was increased for missense mutations [p = 0.0001; odds ratio (OR) = 6.16; confidence interval (CI) = 3.14–13.11], which were more frequent in SNF vs MNFSR (p = 0.0271).